Rate of uncontrolled blood pressure and its associated factors in patients with predialysis chronic kidney disease in Bali, Indonesia - Ni Wayan Kesari Dharmapatni (2020)
© 2019, Ni Wayan Kesari Dharmapatni, Aurawamon Sriyuktasuth and Kanaungnit Pongthavornkamol. Purpose: Hypertension is a key determinant for the development and progression of chronic kidney disease (CKD). The purpose of this study is to assess the rate of uncontrolled blood pressure (BP) and identify its associated factors in patients with predialysis CKD in Bali, Indonesia. Design/methodology/approach: A cross-sectional study was conducted among 165 patients who attended the nephrology clinic in a central public hospital in Bali. Data were obtained by measuring BP at threshold 130/80 mmHg, as well as collected through standardized questionnaires. Univariate analysis was done using Chi-square test, and multivariate analyses were carried out using multiple logistic regression. Findings: A total of 165 patients (111 males and 54 females) with predialysis CKD participated in this study. About 64% of the participants had uncontrolled BP. In multiple logistic regression, all selected variables significantly explained 63.2% of the variance in uncontrolled BP. However, low physical activity (odds ratio [OR] = 24.287, 95% confidence interval [CI]: 3.114–189.445), unhealthy dietary pattern (OR = 10.153, 95% CI: 2.770–37.210), as well as perceived moderate stress (OR = 4.365, 95% CI: 1.024-18.609) and high stress (OR = 10.978, 95% CI: 2.602–46.312) were significantly associated with uncontrolled BP. Research limitations/implications: The study findings provide evidence for health care providers to improve BP control among patients with predialysis CKD. Originality/value: Controlling BP among patients with predialysis CKD was poor. Lifestyle modification and stress management are keys to improving BP control.